PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA - Wahyuni, Sri; Nasar, Adrianus; Kaleka, Melkyanus (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to determine the effect of discovery learning learning model on student physics learning outcomes. The research subjects were 30 students of class X Madrasah Aliyah Muhammadiyah Riung in the 2019/2020 academic year. This type of research is quantitative. Ex-post facto research design that is causal. The data obtained are data on student learning outcomes in physics lessons. Data analysis carried out is normality test and t test. The results of hypothesis testing, obtained data t (countable) 9,403 the value of degrees of freedom is 29. The value of sig. (2-tailed) of 0.000. Significant value (sig. 2-tailed) 0.000 <0.05 then H0 is rejected and H1 is accepted (the proposed hypothesis is accepted). The results of these calculations can be concluded that there is a significant influence on the discovery learning model on the physics learning outcomes of class X Madrasah Aliyah Muhammadiyah Riung.